Prestonellinae—validation of the name as a new subfamily of Bothriembryontidae (Mollusca, Gastropoda, Orthalicoidea) - Bruggen, A.c. Van; Herbert, David G.; Breure, Abraham S.h. (Zootaxa, 2016)
The affinities of the enigmatic South African land snail genus Prestonella Connolly, 1929 were discussed by Herbert (2007) and Herbert & Mitchell (2009), who showed, on the basis of morphological and molecular data, that the genus is referable to the superfamily Orthalicoidea. Currently, the three described species of Prestonella are the only known African representatives of this diverse superfamily. Earlier, van Bruggen (1978) had recognized that these species formed a distinct group and had placed them in the (new) family Prestonellidae. However, as noted by Bouchet & Rocroi (2005: 140), no diagnosis was provided by van Bruggen; the name Prestonellidae thus does not meet the requirements of ICZN Art. 13.1, and is not an available name. In this paper we will redress this issue, also taking into account more recent research which has shed light on the systematic position of this genus within the Orthalicoidea.